PROCESS MODEL OF COMMERCIAL HANDL ING IN AIR TRANSPORT IN RELATION TO AVIATION SECURITY (Perner's Contacts, 2018)
The aim of the article is to analyze weaknesses in which the integrity of the civil aviation security protection system could be impaired. To illustrate the process of commercial passenger and cabin baggage handling in air transport, a graphical scheme of the system was created using the event-driven proces chain model.
Keywords: EPC modelling, aviation security, air transport, commercial handling